Picking up the pieces in Kedah: Tough act: Mukhriz juggling damage control with new programmes - Baharuddin, Noor Adzman (New Straits Times, 2013)
THEY had pledged to make Kolej Universiti Insaniah (Kuin) the best in the country. In doing so, the former Pas-led state government had big plans to turn the state-owned university college into a self-reliant and prestigious private institution of higher learning.